Work Values of Police Officers and Their Relationship With Job Burnout and Work Engagement - Basinska, Beata A.; Dåderman, Anna M. (Frontiers in Psychology, 2019)
Values represent people’s highest priorities and are cognitive representations of basic motivations. Work values determine what is important for employees in their work and what they want to achieve in their work. Past research shows that levels of both aspects of job-related well-being, job burnout and work engagement, are related to work values. The policing profession is associated with high engagement and a risk of burnout. There is a gap in the literature regarding the hierarchy of work values in police officers, how work values are associated with job burnout and work engagement in this group, and whether work values in police officers are sensitive to different levels of job burnout and work engagement. Therefore, the aim of our study was to examine the relationships between work values and job burnout and work engagement, in a group of experienced police officers. We investigated: (a) the hierarchy of work values based on Super’s theory of career development, (b) relationships between work values and burnout and work engagement, and (c) differences between the work values in four groups (burned-out, strained, engaged, and relaxed). A group of 234 Polish police officers completed the Work Values Inventory (WVI) modeled upon Super’s theory, the Oldenburg Burnout Inventory and the Utrecht Work Engagement Scale. The results show that police officers gave the highest priority to extrinsic work values. Job burnout was negatively correlated with the cognitive intrinsic work values (Creativity, Challenge, and Variety), while work engagement was positively correlated with the largest group of intrinsic work values (Creativity, Challenge, Variety, Altruism, and Achievement), as well as with the extrinsic work values (Prestige and Co-workers). The police officers showed significant differences, between levels of job burnout and work engagement, for intrinsic work values such as Variety, Challenge, and Creativity (large effects), and for Altruism and Prestige (moderate effects). The findings are discussed within the context of the Conservation of Resources theory, which explains how people invest and protect their personal resources, and how this is connected with preferred work values. We conclude that intrinsic work values are sensitive to different levels of burnout and engagement.